Positive Solutions for Multipoint Boundary Value Problems for Singular Fractional Differential Equations - Mohamed Jleli; Erdal Karapinar; Bessem Samet (Journal of Applied Mathematics)
A class of nonlinear multipoint boundary value problems for singular fractional differential equations is considered. By means of a coupled fixed point theorem on ordered sets, some results on the existence and uniqueness of positive solutions are obtained.